New Limaiinae (Neuroptera: Chrysopidae) from the early Eocene Fur Formation, Denmark, including an unexpected finding of a Mesozoic genus - Makarkin, Vladimir N.; Perkovsky, Evgeny E. (Zootaxa, 2023)
Two species of Limaiinae (Chrysopidae) are described from the early Eocene Fur Formation of Denmark: Mesypochrysa nielseni sp. nov. and Limaiinae gen. et sp. A. All forewing character states of M. nielseni sp. nov. are similar to those of the widely distributed Mesozoic genus Mesypochrysa Martynov, 1927, which was formerly known from the Middle Jurassic to mid-Cretaceous. Limaiinae gen. et sp. A is represented by an incomplete forewing. Although it differs from other species known from the formation, we refrained to name it pending a more complete specimen. The relatively high diversity of Limaiinae in the early Eocene of Denmark, with at least by two genera and four or five species is surprising. This diversity in the Fur Formation is nearly equal to that of Nothochrysinae.